Drug and Neurofilament Levels in Serum and Breastmilk of Women With Multiple Sclerosis Exposed to Natalizumab During Pregnancy and Lactation - Proschmann, Undine; Haase, Rocco; Inojosa, Hernan; Akgün, Katja; Ziemssen, Tjalf (Frontiers in Immunology, 2021)
Objective To determine the transfer of the monoclonal antibody natalizumab into breastmilk and to evaluate drug and serum neurofilament light chain ((s)NfL) levels in natalizumab exposed pregnancies and lactation periods. Methods Eleven women with relapsing remitting multiple sclerosis treated with natalizumab during pregnancy and lactation were included in this study. Breastmilk samples were collected up to 302 days after delivery and analyzed for natalizumab concentration and NfL. Additionally, maternal drug levels and sNfL were determined preconceptually, in each trimester, at delivery and postpartum. Clinical and radiological disease activity was systemically assessed across pregnancy and postpartum period. Results The mean average natalizumab concentration in breast milk was low at 0.06 µg/ml [standard deviation (SD) 0.05] in the eight patients who provided serial breastmilk samples with an estimated mean absolute infant dose of 0.007 mg/kg/d (SD 0.005). The relative infant dose (RID), a metric comparing the infant with maternal drug exposure was low as well with a mean of 0.04 % (SD=0.03). Most patients had a maximum concentration in breast milk at one to eight days after infusion. Pregnancy was associated with a non-significant decline of the median natalizumab serum concentration. All patients exposed to natalizumab prior (n=10) and during pregnancy (n=11) kept free of disease activity during gestation. While pregnancy was associated with low sNfL levels in patients treated with natalizumab prior and during pregnancy, the postpartum period was linked to a transient sNfL increase in some patients without any evidence of clinical or radiological disease activity. NfL was detectable in the majority of breastmilk samples with a median concentration of 1.7 pg/ml (range 0.004-18.1). Conclusion We determined transfer of natalizumab into breastmilk with an RID far below the threshold of concern of 10%. Studies including childhood development assessment are needed in order to gain safety data about natalizumab-exposed breastfeeding. SNfL assessment might be a useful adjunct to monitor silent disease activity and therapeutic response during pregnancy and postpartum period. However, further investigations regarding transient postpartum sNfL increases are required to determine its association to parturition per se or to a silent disease activity in people with multiple sclerosis.